APPLICATION OF VIBRATIONAL TECHNIQUES IN DETERMINATION OF DYNAMIC PROPERTIES OF AGRICULTURAL PRODUCTS-STATE OF THE ART - Kajuna, Silas T.A.R; Mittal, Gauri S; Silayo, Valerian C.K (Tanzania Journal of Engineering and Technology, 2018)
Abstract